Technology and Health Information Technology in Colorectal Surgery: Electronic Literature Support - Magruder, J. Trent; Efron, Jonathan E. (Clinics in Colon and Rectal Surgery, 2013)
The advent of the Internet has revolutionized the management of reporting and accessing research and data. The authors review the current resources available to surgeons through websites, accumulated published data repositories, and libraries. The change in how we publish and present peer-reviewed data over the last 20 years is also discussed as well as the future of health information technology.
Keywords: MEDLINE; PubMed; Embase; video; website; e-library